2013
DOI: 10.3126/jucms.v1i1.8418
|View full text |Cite
|
Sign up to set email alerts
|

Study of Pathway to Care among Patients with Epilepsy

Abstract: Objective: To assess the pathway to care among patients with epilepsy up to the tertiary care centre Methods: It is a hospital based, cross-sectional descriptive study of 47 patients visiting BPKIHS psychiatry OPD. Written informed consent was taken from the patients and the primary caretaker. A semi structured Performa was used to record the basic sociodemographic details. Pathway Interview Schedule developed by WHO was used to collect the data. Results Majority (66.0%) of subjects were male. Generalized Seiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Regarding the source of information, reason for choice of the first place, common symptoms to visit the first place and susceptibility to the illness; majority (84.8%) were family, (89.7%) were confident, (95.1%) was sudden loss of consciousness and (91.2%) were both rich and poor individuals respectively. This result was consistent with study reported from other studies [ 15 , 23 , 26 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Regarding the source of information, reason for choice of the first place, common symptoms to visit the first place and susceptibility to the illness; majority (84.8%) were family, (89.7%) were confident, (95.1%) was sudden loss of consciousness and (91.2%) were both rich and poor individuals respectively. This result was consistent with study reported from other studies [ 15 , 23 , 26 ].…”
Section: Discussionsupporting
confidence: 94%
“…Amharic version of semi-structured interviewer administered questionnaire involving: socio-demographic, onset and duration of illness, and the adapted ‘Pathway Study’ encounter form, questionnaires, which was designed for use in series of studies to understand care-seeking and treatment pathways of patients with mental disorder were utilized. This form was used among similar study subjects in Africa and India [ 11 , 13 – 15 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Dhami and Jhakri are the faith-based traditional healers [ 29 ]. They are the first point of contact of care in rural areas of the country [ 30 ]. There are public health programs on reproductive health and child morbidity to train the traditional faith healers to refer patients coming to them to the health centers [ 31 ].…”
Section: Discussionmentioning
confidence: 99%